Catalytic enantioselective nucleophilic desymmetrization of phosphonate esters - Formica, M; Rogova, T; Shi, H; Sahara, N; Ferko, B; Farley, AJM; Christensen, KE; Duarte, F; Yamazaki, K; Dixon, DJ (Springer, 2023)
Molecules that contain a stereogenic phosphorus atom are crucial to medicine, agrochemistry and catalysis. While methods are available for the selective construction of various chiral organophosphorus compounds, catalytic enantioselective approaches for their synthesis are far less common. Given the vastness of possible substituent combinations around a phosphorus atom, protocols for their preparation should also be divergent, providing facile access not only to one but to many classes of phosphorus compounds. Here we introduce a catalytic and enantioselective strategy for the preparation of an enantioenriched phosphorus(V) centre that can be diversified enantiospecifically to a wide range of biologically relevant phosphorus(V) compounds. The process, which involves an enantioselective nucleophilic substitution catalysed by a superbasic bifunctional iminophosphorane catalyst, can accommodate a wide range of carbon substituents at phosphorus. The resulting stable, yet versatile, synthetic intermediates can be combined with a multitude of medicinally relevant O-, N- and S-based nucleophiles.